Necesidad de implementar el uso de licencia y matrícula para la circulación de scooters de alta potencia en cumplimiento al artículo 90 de la Ley Orgánica de Transporte Terrestre, Tránsito y Seguridad Vial - Santana Coveña, Sandra Cristina (2022)
From an objective point of view, the electric scooter is a vehicle that works with a motor as a means of propulsion and aims to offer a sustainable solution to various problems. Electric scooters improve vehicular congestion and urban pollution, help people who must move from home to work and vice versa, or run daily errands, giving them the option to move around their cities in a fast, accessible and convenient way, while reducing their carbon footprint. In stone cases electric scooters avoid emitting up to 1600kg of CO2 or more, becoming an alternative to private cars or motorcycles for intra-urban trips since they avoid the classic traffic problems during peak hours and parking. The electric scooter is a small, light vehicle compared to a conventional motorcycle, easy to maneuver, and like other vehicles regulated by traffic laws, they travel through the country's road networks and have the particularity of being able to carry a passenger. However, it is considered that they do not circulate in the proper way because it is not guaranteed that the driver of this type of vehicle has knowledge of traffic laws, and they do not carry safety measures such as helmets. Moreover, because they are electric, they are silent vehicles which constitutes a danger both for themselves and for society. For this reason, in this thesis work, a reform is proposed so that the use of these electric scooters is regulated and they are subject to the traffic laws of our country in 2 ways. Electric scooter operators would be required to follow a training course and obtain a driving license; and the electric scooter vehicle would need to be registered.